2021
DOI: 10.2147/jpr.s278285
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin Blockade in the Treatment of Painful Vaso-Occlusive Crises in Sickle Cell Disease: A Spotlight on Crizanlizumab

Abstract: Microvascular vaso-occlusion driven pain crisis is the hallmark of sickle cell disease with profound morbidity and increased mortality. Selectins, most notably P-selectins have an integral role in this phenomenon. P-selection was first identified in 1989. In 2019, after 3 decades of basic, translational, and clinical work with this pathway, the US Food and Drug Administration approved a P-selectin antibody, crizanlizumab to reduce frequency of pain crisis in patients more than 16 years with sickle cell disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Endothelial cells in Sickle Cell Disease (SCD) express P-selectin on a long-term basis [ 11 ]. P-selectin upregulation in endothelial cells and platelets contributes to cell–cell interactions implicated in the development of vaso-occlusion and sickle cell pain crises [ 12 ]. P-selectin levels in the blood have been found to be elevated in a variety of acute and chronic cardiovascular diseases, including peripheral arterial disease, coronary artery disease, hypertension, and acute myocardial infarction [ 13 , 14 , 15 , 16 , 17 ].…”
Section: P-selectin In Human Diseasesmentioning
confidence: 99%
“…Endothelial cells in Sickle Cell Disease (SCD) express P-selectin on a long-term basis [ 11 ]. P-selectin upregulation in endothelial cells and platelets contributes to cell–cell interactions implicated in the development of vaso-occlusion and sickle cell pain crises [ 12 ]. P-selectin levels in the blood have been found to be elevated in a variety of acute and chronic cardiovascular diseases, including peripheral arterial disease, coronary artery disease, hypertension, and acute myocardial infarction [ 13 , 14 , 15 , 16 , 17 ].…”
Section: P-selectin In Human Diseasesmentioning
confidence: 99%
“…This line of research could result in novel platelet-based (e.g. P-selectin blocking agents [32]) interventions for the prevention and treatment of MetS-related cognitive impairment.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…They also observed that the SELP-PSGL-1 axis drove microglia towards a more immunosuppressive phenotype with increased expression of ARG-1, IL-10 and TGB-β in animal studies [ 130 ]. Despite these promising preclinical results, and although P-selectin monoclonal antibody is accepted by FDA for use in sickle cell anemia to prevent pain crisis [ 190 ], clinical trials are not yet being initiated for glioma treatment.…”
Section: Therapeutic Options For Targeting Tamsmentioning
confidence: 99%